2020
DOI: 10.3389/fcimb.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Protection Elicited by a DNA Vaccine Candidate Expressing the prM-E Antigen of Dengue Virus Serotype 3 in Mice

Abstract: Dengue virus (DENV) is the causative agent of dengue, and its incidence has increased 30-fold in the past five decades. Among the four cocirculating serotypes, DENV3 is associated with an increased number of severe infections and has become widespread. Vaccination is the mainstay of prevention in reducing disease burden. Previously, the protective efficacy of DNA vaccine candidates toward DENV1, 2, and 4 was confirmed in mice. In this study, a DNA vaccine candidate (pVAX1-D3ME) expressing the prM and E protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Further, pVax1 features a kanamycin resistance gene for selection to avoid allergic responses associated with ampicillin as well as a human CMV promoter and BGH polyadenylation signal for efficient DNA expression and mRNA transcription termination, respectively [ 18 ]. Recently, the vector has been used in platforms showing enhanced protection from Japanese Encephalitis Virus, influenza H9N2, Dengue virus, Crimean-Congo Hemorrhagic Fever Virus, and anti-tumor applications, [ 19 , 20 , 21 , 22 , 23 ]. These DNA vaccines were able to elicit high titers of protective antibody [ 19 , 20 , 21 , 22 ] suggesting this approach may also be effective for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, pVax1 features a kanamycin resistance gene for selection to avoid allergic responses associated with ampicillin as well as a human CMV promoter and BGH polyadenylation signal for efficient DNA expression and mRNA transcription termination, respectively [ 18 ]. Recently, the vector has been used in platforms showing enhanced protection from Japanese Encephalitis Virus, influenza H9N2, Dengue virus, Crimean-Congo Hemorrhagic Fever Virus, and anti-tumor applications, [ 19 , 20 , 21 , 22 , 23 ]. These DNA vaccines were able to elicit high titers of protective antibody [ 19 , 20 , 21 , 22 ] suggesting this approach may also be effective for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the vector has been used in platforms showing enhanced protection from Japanese Encephalitis Virus, influenza H9N2, Dengue virus, Crimean-Congo Hemorrhagic Fever Virus, and anti-tumor applications, [ 19 , 20 , 21 , 22 , 23 ]. These DNA vaccines were able to elicit high titers of protective antibody [ 19 , 20 , 21 , 22 ] suggesting this approach may also be effective for COVID-19. Importantly, none of these studies reported negative side effects associated with use of the pVax1 vector [ 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following these and other reports presenting promising results with monovalent prM/E-based pVAX constructions (99)(100)(101)(102), a new tetravalent formulation was developed by cloning sequences of Hawaii, Tr1751 strain, H87 and H241 strains from DENV1 to 4, respectively (TetraME) (78, 102). A 3-dose scheme of 50 µg of each monovalent DNA vaccine administered by electroporation in BALB/c mice induced T-cell activation with high IL-4 and IFN-γ production, long-term NAb response against all the four serotypes, and animals survived monovalent DENV1-4 challenges (78).…”
Section: Dengue Dna Vaccines Vaccines Based On Prm and E Proteinsmentioning
confidence: 99%
“…This information added with the fact that Pla is not an effective immunogen and is not a protective antigen in mice suggest that the absence of pla should not decrease the efficacy of a live plague vaccine while increasing its safety. Consistent with this idea, different vaccine strains were engineered [ 147 , 148 , 149 , 150 ]. One of them, lacking the Braun lipoprotein, the lipid A biosynthesis myristoyltransferase and Pla (i.e., a Δ lpp Δ msbB Δ pla strain), confers long-term humoral and cell-mediated immune responses and full protection against pneumonic plague in rats [ 149 ].…”
Section: Pla: Not a Vaccine Antigen Maybe An Antibacterial Targetmentioning
confidence: 99%